Evaluación fisicoquímica del tratamiento primario de agua, mediante el uso de un coagulante obtenido a partir de residuos de café (2018)
In the cultivation of the coffee, green fruit residues are present, these residues can be exploited by their phenolic contents 12 . In this research, a coagulant was evaluated from coffee bean of species coffea arabica coffee residues in natural water samples from the Carbonera creek, in the Subía village, in the municipality of Silvania - Cundinamarca. Taking into account initial and final parameters of the Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD) and turbidity. The initial turbidity data for the creek during the dry season and rain corresponded to 3.86 and 367 NTU. Subsequently, the coagulant extraction process was performed using the ultrasound-assisted extraction technique for a time of 60 minutes and 40kHz; The final concentration of polyphenols was determined by the Follin Ciocalteu quantification method, obtaining an extract concentration of 385.4 mg GAE / g of coffee on a dry basis.